A Rare Case of Dissemination of Primary Spinal Glioblastoma - Sirinoglu, Deniz; Sarigul, Buse; Baskurt, Ozan; Aydin, Mehmet Volkan (Indian Journal of Neurosurgery, 2021)
Background Primary spinal glioblastoma is a rare lesion which constitutes only 1.5% of all spinal tumors. Diagnosis is challenging due to absence of any radiological hallmark of the disease. Even though surgery combined with chemoradiotherapy is the optimal management for these tumors, prognosis is still poor. Dissemination of glioblastoma is reported several times in the literature, which is correlated with worse prognosis and outcome. This case report that we are presenting is the first case where dissemination of primary spinal glioblastoma dissemination is limited only to spinal cord, without intracranial invasion, and regression was achieved with chemoradiotherapy.Case Report In this article, a patient with primary spinal glioblastoma who presented with paraparesia is presented. Patient underwent surgery for resection of the tumor and received adjuvant radiotherapy. However, 9 months postoperatively, dissemination was detected in epidural and subdural spaces of spinal canal, with concomitant compression of spinal cord. There was no radiographically detected lesion in cranial MRI. He underwent second session of radiotherapy, combined with chemotherapy and steroid. Five months later, regression of metastatic disseminated lesions was observed.Conclusion Primary spinal glioblastoma is a rare pathology and known to have a poor prognosis, notably with dissemination of the disease. Even though further biomolecular studies are necessary to explain the pathophysiology better, chemotherapy and radiotherapy may be effective in regression of disseminated lesions.
Keywords: spinal glioblastoma; dissemination; intramedullary tumor